Differential expression of genes involved in response to cold stress in Solanum tuberosum subsp. andigena - Martinez, Diana (2018)
Freezing is abiotic stress characterized by a decrease air temperature below zero degrees Celsius. It is one of the highest incidence and impact problems in Andean´s agriculture. Morphological and physiological studies indicate that native potatoes are sources of genes related to plant frost tolerance. However, the molecular bases of tolerance mechanisms in potato are still unknown. RNA sequencing technology (RNA-seq) is an excellent tool to identify genes expression profile changes after freezing stress. In this work, the transcriptome of a freezing tolerant and another susceptible variety of potato were sequenced and compared after exposition to freezing stress (-8 °C) for an hour, using the RNA-seq technique to identify differences in the genes expression between both varieties. It was observed that more than 199 million reads were aligned against the reference genome (Solanum tuberosum Group Phureja), which correspond to 82.1% of the total reads obtained after sequencing. The tolerant variety showed the highest number of Differentially Expressed Genes (DEGs) up-expressed (262 DEGs), while the susceptible variety showed the highest number of down-expressed DEGs (37 DEGs).